Immunosuppressive role of γδ T cells in cancer: the other side of the coin - Patil, Rushikesh; Sureshbabu, Shalini Kashipathi; Chiplunkar, Shubhada V. (Translational Cancer Research; Vol 6, Supplement 1 (February 28, 2017): Translational Cancer Research, 2017)
Development of cancer is associated with evolution of tumor microenvironment which subverts the immune response for its benefit. The tumor environment promotes the production of proinflammatory cytokines, leading to the accumulation of suppressive cells that inhibit antitumor immunity. In contrast, strong lymphocyte infiltration has been reported to be associated with an antitumor response and improved clinical outcome (1).